2003
DOI: 10.1097/01.tp.0000063219.21313.32
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus ans an early predictive factor in patients with acute liver failure1

Abstract: Hypophosphatemia and early phosphorus administration are associated with a good prognosis in ALF, whereas hyperphosphatemia is predictive of poor recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 26 publications
0
57
0
3
Order By: Relevance
“…Furthermore, a contemporary analysis of 719 major liver resections also reported increased postoperative morbidity and mortality associated with the lack of HP rather than its presence (27). Our findings suggest that, rather than bearing an (28). Finally, the only other large contemporary analysis of post-hepatectomy HP indicated that patients presenting an elevated phosphate on postoperative day 2 were at higher risk of liver insufficiency (27).…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, a contemporary analysis of 719 major liver resections also reported increased postoperative morbidity and mortality associated with the lack of HP rather than its presence (27). Our findings suggest that, rather than bearing an (28). Finally, the only other large contemporary analysis of post-hepatectomy HP indicated that patients presenting an elevated phosphate on postoperative day 2 were at higher risk of liver insufficiency (27).…”
Section: Discussionmentioning
confidence: 68%
“…169,171 The significance of hypophosphataemia after hepatic surgery has been debated. Some studies suggest that low phosphate indicates better prognosis, 172 while others suggest that it may delay postoperative recovery. 70 However, replacement of phosphate has been shown to improve recovery of hepatic function.…”
Section: Increased Lossmentioning
confidence: 99%
“…In fact, it is illusory to think that a single set of criteria is relevant to FH of any cause. For this reason, a specific score according to the aetiology has been proposed: non-paracetamol-induced ALF in KCH criteria, blood arterial lactate [47], serum phosphate [48] [49], α-fetoprotein [50] in paracetamol-induced ALF, prognostic factors for HAV infection-related FH [51], a prognostic scoring model for liver transplantation in patients with non-paracetamol-related ALF [52], prognostic factors of Amanita phalloides poisoning [53] [54].…”
Section: Liver Transplantmentioning
confidence: 99%